An MR-compatible antenna and application in a murine superficial hyperthermia applicator. (18th August 2018) - Raaijmakers, Elles A. L.; Mestrom, Rob M. C.; Sumser, K.; Salim, Ghassan; van Rhoon, Gerard C.; Essers, Jeroen; Paulides, Margarethus M.
Abstract: In this work, a novel magnetic resonance (MR)-compatible microwave antenna was designed and validated in a small animal superficial hyperthermia applicator. The antenna operates at 2.45 GHz and matching is made robust against production and setup inaccuracies. To validate our theoretical concept, a prototype of the applicator was manufactured and tested for its properties concerning input reflection, sensitivity for setup inaccuracies, environment temperature stability and MR-compatibility. The experiments show that the applicator indeed fulfils the requirements for MR-guided hyperthermia investigation in small animals: it creates a small heating focus (<1 cm 3 ), has a stable and reliable performance (S11 < −15 dB) for all working conditions and is MR-compatible.